America in the Nineties - Serrianne, Nina Esperanza (Book collections on Project MUSE., 2015)
This book is a survey treatment of the 1990s. The trajectory of the narrative follows from the fall of the Berlin Wall in 1989 to the terrorist attacks of September 11, 2001. This book seeks to give a voice to historically marginalized communities, while providing an overview of the 1990s. The analysis includes examinations of: the end of the 1980s, America's War in the Gulf, Bush's domestic agenda; The 1992 Campaign, Clinton's domestic agenda; The United States and genocide; globalization; science and technology; pop culture; race relations; LGBT and women's right; and the scandals of the Clinton Administration. The book strikes the balance between providing an analysis of the 1990s, while providing the reader with basic key information about the decade. This book is one of the first of its kind to examine the whole decade and while providing an analysis on a multitude of subjects.